A Monocephalus Diprosopus Fetus: Antenatal Sonographic Findings - Kavak, Salih Burçin; Kavak, Ebru Çelik; Coskun, Berna; İlhan, Raşit; Orak, Uğur (My University, 2015)
Monocephalus Diprosopus is the rarest form of conjoined twins. The etiology of this anomaly is stil obscure. We herein report a monocephalus diprosopus case that was diagnosed in week 19 of pregnancy was presented due to its rarity and the significance of its prenatal diagnosis. Recommended a pregnancy termination since it does not have a definitive treatment today, prenatal diagnosis made for such fetuses at an early stage bears importance in terms of lowering the severity of psychological trauma.
Keywords: Pediatri; Anatomi ve Morfoloji